Effects of green tea based oral health strategies on disease activity in rheumatoid arthritis - Lan, Sanrong; Jin, Shuang; Lin, Rong; Chen, Baochuan; Gao, Fei; Zhang, Shengli; Chen, Lili; Li, Hong (Frontiers in Medicine, 2024)
Aim: In this study, we aimed to evaluate oral health strategies in rheumatoid arthritis (RA) patients with periodontitis.We enrolled 110 RA patients with periodontitis who were diagnosed in a Grade A tertiary hospital into an oral health strategies program. The control and test groups comprised 55 cases each. The management effect was evaluated by self-care ability, oral health-related quality of life, RA-related clinical indicators, and the DAS28 score. The control group received routine nursing, whereas the test group was in a self-health management program for 3 months.Results: After the intervention, compared to the control group, the test group showed better self-care ability, oral health-related quality of life score, RA-related clinical indicators, and DAS28 score (P < 0.05).Our oral health strategies program slowed down the progression of the disease and can be popularized in patients.